68Ga-PSMA PET/CT in the evaluation of bone metastases in prostate cancer - Sachpekidis, Christos; Kopka, Klaus; Hadaschik, Boris; Hohenfellner, Markus; Haberkorn, Uwe; Dimitrakopoulou-Strauss, Antonia (European journal of nuclear medicine and molecular imaging, 2018)
PurposeThe aims of this retrospective analysis were to compare 68Ga-PSMA PET findings and low-dose CT findings (120 kV, 30 mA), and to obtain semiquantitative and quantitative 68Ga-PSMA PET data in patients with prostate cancer (PC) bone metastases.MethodsIn total, 152 PET/CT scans from 140 patients were evaluated. Of these patients, 30 had previously untreated primary PC, and 110 had biochemical relapse after treatment of primary PC. All patients underwent dynamic PET/CT scanning of the pelvis and lower abdomen as well as whole-body PET/CT with 68Ga-PSMA-11. The PET/CT scans were analysed qualitatively (visually), semiquantitatively (SUV), and quantitatively based on a two-tissue compartment model and a noncompartmental approach leading to the extraction of the fractal dimension. Differences were considered significant for p values <0.05.ResultsIn total, 168 68Ga-PSMA-positive and 113 CT-positive skeletal lesions were detected in 37 patients (8 with primary PC, 29 with biochemical recurrence). Of these 168 lesions, 103 were both 68Ga-PSMA PET-positive and CT-positive, 65 were only 68Ga-PSMA-positive, and 10 were only CT-positive. The Yang test showed that there were significantly more 68Ga-PSMA PET-positive lesions than CT-positive lesions. Association analysis showed that PSA plasma levels were significantly correlated with several 68Ga-PSMA-11-associated parameters in bone metastases, including the degree of tracer uptake (SUVaverage and SUVmax), its transport rate from plasma to the interstitial/intracellular compartment (K1), its rate of binding to the PSMA receptor and its internalization (k3), its influx rate (Ki), and its distribution heterogeneity.Conclusion68Ga-PSMA PET/CT is a useful diagnostic tool in the detection of bone metastases in PC. 68Ga-PSMA PET visualizes more bone metastases than low-dose CT. PSA plasma levels are significantly correlated with several 68Ga-PSMA PET parameters.
Im Titel ist "68" in 68Ga-PSMA PET/CT hochgestellt
Gesehen am 10.05.2019